2016
DOI: 10.1021/acsami.5b12600
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of Plasma Proteins Using a Quartz Crystal Microbalance

Abstract: Proteins that get adsorbed onto the surfaces of biomaterials immediately upon their implantation mediate the interactions between the material and the environment. This process, in which proteins in a complex mixture compete for adsorption sites on the surface, is determined by the physicochemical interactions at the interface. Competitive adsorption of bovine serum albumin (BSA), fibronectin (Fn), and collagen type I (Col I), sequentially and from mixtures, was investigated so as to understand the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 61 publications
(158 reference statements)
3
33
1
Order By: Relevance
“…This behavior was enhanced in the case of MGTg substrate due to the presence of epoxide groups on the surface, which may mediate the binding of these proteins. These findings show that the functional groups can selectively increase the adsorption of proteins, and corroborates the previously reported results . Moreover, studies with QCM‐D have revealed that an increase in the viscoelastic properties of the adsorbed Fn layer correlates to the unfolding of the molecule once is adsorbed on the surface, increasing the exposure of the RGD cell binding sites and in consequence enhancing the bioactivity of the protein .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This behavior was enhanced in the case of MGTg substrate due to the presence of epoxide groups on the surface, which may mediate the binding of these proteins. These findings show that the functional groups can selectively increase the adsorption of proteins, and corroborates the previously reported results . Moreover, studies with QCM‐D have revealed that an increase in the viscoelastic properties of the adsorbed Fn layer correlates to the unfolding of the molecule once is adsorbed on the surface, increasing the exposure of the RGD cell binding sites and in consequence enhancing the bioactivity of the protein .…”
Section: Discussionsupporting
confidence: 91%
“…While BSA, because of its non-specific adsorption, displays lower affinity toward coated surfaces, Fbg and Fn do not. 45 Opposite effect was observed for the adsorption profile of Fbg, Fn, and Col I, where MGTg in spite of being slightly smoother than the other surfaces, adsorbed higher amounts of protein. More interestingly, the proteins involved in the subsequent cell attachment process due to their cell binding domains, such as Fn and Col I, adsorbed preferably onto developed siloxane coatings compared to Ti control.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…FN adheres less tightly to the annealed PEMs as observed by gamma counting. [51][52][53] The selective increase of BSA adsorption upon annealing suggests that the extrapolation of the behavior of Adv. We can only hypothesize that the increase in hydrophilicity and the presence of very narrow fibrils in the PEM after annealing do not facilitate tight attachment of FN to the PEM.…”
Section: Discussionmentioning
confidence: 99%